Posttraumatic Stress Symptoms Among National Guard Soldiers Deployed to Iraq: Associations with Parenting Behaviors and Couple Adjustment - Gewirtz, Abigail H. (2010)
OBJECTIVE: This article reports findings from a one-year longitudinal study examining the impact of change in PTSD symptoms following combat deployment on National Guard soldiers’ perceived parenting, and couple adjustment one year following return from Iraq. METHOD: Participants were 468 Army National Guard fathers from a Brigade Combat Team (mean age 36 years; median deployment length 16 months; 89% European American, 5% African American, 6% Hispanic American). Participants completed an in-theater survey one month before returning home from OIF deployment (Time 1), and again, one year post-deployment (Time 2). The PTSD Checklist-Military Version (PCL-M; Weathers, Litz, Herman, Huska, & Keane, 1993) was gathered at both times, and two items assessing social support were gathered at baseline only. At Time 2, participants also completed self-report measures of parenting (Alabama Parenting Questionnaire—Short Form; Elgar, Waschbusch, Dadds, & Sigvaldason, 2007), couple adjustment (Dyadic Adjustment Scale-7; Sharpley & Rogers, 1984; Spanier, 1976), parent-child relationship quality (4 items from the Social Adjustment Scale-Self Report; Weissman & Bothwell, 1976), alcohol use (Alcohol Use Disorders Identification Test; Babor, Higgins-Biddle, Saunders, & Monteiro, 2001), and items assessing injuries sustained while deployed. RESULTS: Structural equation modeling analyses showed that increases in PTSD symptoms were associated with poorer couple adjustment and greater perceived parenting challenges at Time 2 (both at p<.001). Furthermore, PTSD symptoms predicted parenting challenges independent of their impact on couple adjustment. CONCLUSIONS: Findings highlight the importance of investigating and intervening to support parenting and couple adjustment among combat-affected National Guard families.